2012
DOI: 10.1145/2452537.2452546
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the real-time capabilities of the Linux kernel

Abstract: The mainline Linux Kernel is not designed for hard real-time systems; it only fits the requirements of soft real-time systems. In recent years, a kernel developer community has been working on the PREEMPT-RT patch. This patch (that aims to get a fully preemptible kernel) adds some real-time capabilities to the Linux kernel. However, in terms of scheduling policies, the real-time scheduling class of Linux is limited to the First-In-First-Out (SCHED_FIFO) and Round-Robin (SCHED_RR) scheduling policies. These sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
6
1
1
Order By: Relevance
“…In the context of slot-based task-splitting scheduling algorithms, although some practical works (Sousa et al 2010(Sousa et al , 2011a(Sousa et al , 2012Bastoni et al 2011) have clearly demonstrated that these scheduling schemes are practical to implement in a real system, the practice also shows some performance degradation compared to what is theoretically achievable, due to various sources of overheads often unaccounted for by the theory. For instance, most theoretical works assume that task switching is instantaneous, but, in practice, it is time consuming because the operating system has to save the state of one task and restore that of another task.…”
Section: Contribution Of This Articlementioning
confidence: 99%
See 3 more Smart Citations
“…In the context of slot-based task-splitting scheduling algorithms, although some practical works (Sousa et al 2010(Sousa et al , 2011a(Sousa et al , 2012Bastoni et al 2011) have clearly demonstrated that these scheduling schemes are practical to implement in a real system, the practice also shows some performance degradation compared to what is theoretically achievable, due to various sources of overheads often unaccounted for by the theory. For instance, most theoretical works assume that task switching is instantaneous, but, in practice, it is time consuming because the operating system has to save the state of one task and restore that of another task.…”
Section: Contribution Of This Articlementioning
confidence: 99%
“…This new schedulability analysis supersedes all previous utilization-based analyses. Further, it defines new schedulability tests that incorporate all real-world overheads incurred by implementations of the S-EKG and NPS-F algorithms (Sousa et al , 2012.…”
Section: New Demand-based and Overhead-aware Schedulability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, over the years, many of the improvements designed and developed by the PREEMPT_RT project (documentation is maintained on the Linux Foundation Wiki [1]) are now part of the mainline Linux kernel according to the Linutronix Co. [2]. In the past, approaches that have been considered in providing a Linux kernel with real-time capabilities, either improve the Linux kernel itself so that it provides bounded latencies for real-time applications (e.g., the PREEMPT_RT project) or add a layer below the Linux kernel (co-kernel approach) that handles all the realtime requirements separately (e.g., RTLinux, RTAI and Xenomai) [3][4][5]. Regarding latency issues, although RTAI and Xenomai offer lower latency than PREEMPT_RT, Linutronix tests show that the differences are not so significant, especially in real-world scenarios.…”
Section: Introductionmentioning
confidence: 99%